Identification of the key targets for sepsis-associated acute kidney injury by RNA sequencing combined with bioinformatics methods - Linghan Leng; Chenglin Wang; Yaxing Deng; Yingchun Hu (BMC Immunology)
Abstract Purpose This research probes into genes related to the risk of concurrent kidney injury in septic patients to provide reliable targets for early identification of sepsis-associated kidney injury and prognosis research. Methods Peripheral blood samples were isolated from 10 healthy individuals and 22 septic patients for RNA sequencing and differential analyses. Meanwhile, the top 1000 kidney-associated genes were chosen from the GTEx website. Subsequently, DEGs in sepsis were intersected with kidney-specific genes, followed by GO and KEGG analyses on these intersection genes. The predictive ability of hub genes for prognosis was evaluated using survival analysis. A meta-analysis was carried out to determine the differential expression profiles of hub genes between the sepsis surviving and dead groups. ROC curves were plotted to screen hub genes and clarify their diagnostic value. Cell line localization of hub genes was further clarified through single-cell RNA sequencing. Results There were 40 targets in the intersection between 1328 DEGs in sepsis and 1000 kidney-associated genes. These intersection genes were mainly engaged in functions and signaling pathways .Survival curves linked the higher levels of CD74 and IL32 to raised survival rates of patients, indicating positive correlations of CD74 and IL32 with patient prognosis. Meta-analysis revealed that CD74 and IL32 were highly expressed in the sepsis surviving group but poorly expressed in the sepsis dead group, showing statistically significant differences between these two groups. In the ROC analysis of hub genes, AUC values of CD74 (0.983) and IL32 (0.980) suggested their high diagnostic value. Lastly, CD74 was principally expressed in macrophages, while IL32 was mainly presented in T cells. Conclusion CD74 and IL32, as biomarkers for early diagnosis and prognostic evaluation of sepsis complicated with kidney injury, are highly expressed in macrophages and T cells, respectively, providing new diagnostic and prognostic targets for sepsis complicated with acute kidney injury.